2022
DOI: 10.3389/fonc.2022.812598
|View full text |Cite|
|
Sign up to set email alerts
|

Blockade of Uttroside B-Induced Autophagic Pro-Survival Signals Augments Its Chemotherapeutic Efficacy Against Hepatocellular Carcinoma

Abstract: Our previous study has demonstrated that Uttroside B (Utt-B), a saponin isolated from the leaves of Solanum nigrum Linn induces apoptosis in hepatic cancer cells and exhibits a remarkable growth inhibition of Hepatocellular Carcinoma (HCC). Our innovation has been granted a patent from the US (US 2019/0160088A1), Canada (3,026,426.), Japan (JP2019520425) and South Korea (KR1020190008323) and the technology have been transferred commercially to Q Biomed, a leading US-based Biotech company. Recently, the compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Our previous study screened cancer cells of various origins for their cytotoxicity towards Utt-B, wherein, the HCC cells exhibited remarkable cytotoxic potential [ 13 ]. Our very recent study has unraveled, with mechanism-based evidence, better modes to further improve the chemotherapeutic potential of Utt-B against HCC [ 9 ]. Except for a couple of in silico observations, there are no reports on the biological activity of Utt-B, other than ours, to date.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study screened cancer cells of various origins for their cytotoxicity towards Utt-B, wherein, the HCC cells exhibited remarkable cytotoxic potential [ 13 ]. Our very recent study has unraveled, with mechanism-based evidence, better modes to further improve the chemotherapeutic potential of Utt-B against HCC [ 9 ]. Except for a couple of in silico observations, there are no reports on the biological activity of Utt-B, other than ours, to date.…”
Section: Discussionmentioning
confidence: 99%
“…The current study depicts Utt-B as a better anti-HCC chemotherapeutic in comparison with sorafenib, the standard drug used to treat the disease. Our previous studies demonstrated the exceptional anti-HCC efficacy of Utt-B, which is a strong inducer of caspase-mediated apoptosis [ 9 , 13 ]. However, a comparative evaluation of the anti-HCC potency of Utt-B with sorafenib, the most studied US FDA-approved drug against HCC, was a requisite for better apprehension [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations